The Effectiveness of Religious Coping Training in Reducing Academic Stress in New Students - Abd. Hamid Cholili; Lincha Ayu Triana Dewi; Anugrah Cahyani Prastowo; Wasilatul Kamilahi; Idza Athifatu Rahmania; M. Mahbubi (Fenomena, 2024)
New students often face high levels of academic stress due to the heavy academic demands in their early college years. Previous studies have discussed stress management strategies, but little attention has been given to the effectiveness of structured religious coping training as a preventive intervention. This study aims to examine whether religious coping training can reduce academic stress in new students. A pre-experimental design was employed, using a modified version of the Student Life Stress Inventory (SLSI) consisting of 51 items as the measurement tool. Data were analyzed through descriptive statistics and paired sample t-test. The results revealed a significant reduction in academic stress levels after the intervention. The average pretest score was 95.57, which decreased to 69.14 in the posttest, with a mean difference of 26.43. The t-test results confirmed the statistical significance of this decrease (p < 0.05). These findings indicate that religious coping training is effective in helping new students manage academic stress. This study contributes both theoretically, by reinforcing the role of religious coping in stress management, and practically, by offering a structured training model that can be applied in higher education settings. Mahasiswa baru sering menghadapi tingkat stres akademik yang tinggi akibat banyaknya tuntutan akademik pada tahun pertama perkuliahan. Beberapa penelitian sebelumnya telah membahas strategi manajemen stres, namun masih sedikit yang menguji efektivitas pelatihan koping religius secara terstruktur sebagai intervensi preventif. Penelitian ini bertujuan untuk menguji apakah pelatihan koping religius dapat menurunkan stres akademik pada mahasiswa baru. Penelitian menggunakan desain pra-eksperimental dengan instrumen Student Life Stress Inventory (SLSI) versi modifikasi yang terdiri dari 51 item. Analisis data dilakukan dengan statistik deskriptif dan uji t-berpasangan. Hasil penelitian menunjukkan adanya penurunan signifikan pada tingkat stres akademik setelah intervensi. Rata-rata skor pretest sebesar 95,57 menurun menjadi 69,14 pada posttest, dengan selisih 26,43. Hasil uji-t mendukung temuan ini dengan tingkat signifikansi (p < 0,05). Temuan ini menunjukkan bahwa pelatihan koping religius efektif dalam membantu mahasiswa baru mengelola stres akademik. Penelitian ini memberikan kontribusi secara teoretis dengan memperkuat peran koping religius dalam manajemen stres, serta secara praktis dengan menawarkan model pelatihan yang dapat diterapkan di lingkungan perguruan tinggi.